Impact of radiotherapy on the bond strength of different adhesive systems to human dentin - Renally Bezerra Wanderley Lima; Maria Luiza Pontual; Venâncio Fernandes Dantas; Sônia Saeger Meireles; Ana Karina Maciel Andrade; Rosângela Marques Duarte (Universidade Estadual de Campinas, 2019)
Aim: The aim of this study is to evaluate the effect of radiotherapy on the bond strength of resin-based composite restorations to dentin, performed either 24 h or 1 year before or after radiation. Methods: Ninety-six posterior teeth were randomly distributed into the following groups: IB (n = 16), irradiated teeth were restored 1 year after x-ray application; NB (n = 16), not irradiated teeth were stored for 1 year and then restored. IA (n = 32), teeth were restored and irradiated at 24 h or 1 year after the restoration. NA (n = 32), teeth were restored, not irradiated, and tested as IA. Eight samples from each group were randomly assigned to either the three-step or two-step etch-and rinse adhesive system procedure. The irradiated specimens were subjected to 60 Gy of x-ray radiation fractionally. The restored teeth were vertically sectioned, and 1-mm2 resin-dentin sticks were obtained and submitted to the microtensile bond strength test. The bond strength data were analyzed by two-way analysis of variance (ANOVA) followed by Tukey's test (p < 0.05). Failure modes were examined by optical microscopy and scanning electron microscopy. Results: The IB group showed lower bond strength values compared to the NB group. The bond strength values between the adhesive systems were not statistically different. Conclusion: The application of radiation dose decreased the bond strength of the adhesive restorations to dentin when the bonding procedure was conducted 1 year after in vitro radiotherapy.